Penerapan Metode Analytical Hierarchy Process dalam Analisis Profil Badan Usaha Milik Negara Tempat Kerja bagi Lulusan Program Studi Matematika - Suci Rizka Welza Putri; Minora Longgom Nasution; Muhammad Subhan (Journal of Mathematics UNP, 2014)
Abstract The goal of this research is to know about main criteria that is considered by the graduate of Mathematics Study Program, Faculty of Mathematics and Science, State University of Padang in choosing a job in Badan Usaha Milik Negara (BUMN) using Analytical Hierarchy Process (AHP) method. The data is collected from opinion of respondents which is the September 2012 period graduates in pairwise comparison questionnaire form using Saaty’s scale (1-9). The main result of this research is the graduate is more consider about their carrier in the future (31,2%) in the BUMN Persero that they choose, then followed bysalary, image and placement. Then the other one shows that Pertamina (34,5%) is  the first priority as a job choice, followed by Perusahaan Listrik Negara, Telkom, Garuda Indonesia, Bank Tabungan Negara, Pos Indonesia, Asuransi Jasa Raharja, and the last one is Pembangunan Perumahan. Keywords Analytical Hierarchy Process, priority, job choice